EARLY RENAL FAILURE AFTER MESALAZINE (CASE REPORT) - Musil, Dalibor; Tillich, Josef (Biomedical papers, 2000)
An early onset of asymptomatic renal failure in a young man with ulcerative colitis treated with high-dosemesalazine is the subject of this case report. After mesalazine withdrawal, renal function was quickly restored. Incontrast with published case reports, the onset of renal impairment occurred very early. Serum urea reachedpathological values 27 days and serum creatinine 15 days after mesalazine treatment was started. The diagnosis ofrenal impairment was supported by urine analysis (both semi-quantitative and quantitative) and dynamic renalisotope scanning.
Keywords: 5-Aminosalicylic acid / Mesalazine / Renal failure / Tubuloinerstitial nephritis / Ulcerative colitis